Gambaran Kadar Hemoglobin dan Karbon Monoksida pada Pedagang Sate - Yuvita; Asti Mulasari, Surahma; Suryani, Dyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Background: Satay smoke contains a pollutant called carbon monoxide (CO). Carbon monoxide (CO) is a colorless and odorless substance, but contains toxins that can adversely affect human health, especially will affect hemoglobin levels in the body. This systematic review of literature review aims to describe hemoglobin and carbon monoxide (CO) levels in satay traders. This research is a literature review, so the data base used in searching this article uses secondary sources derived from google scholar and sage publications with the keywords